KETIMPANGAN SPASIAL PEMBANGUNAN EKONOMI DAN MODAL MANUSIA DI PULAU JAWA: PENDEKATAN EXPLATORY SPATIAL DATA ANALYSIS - ANWAR, AMINUDDIN (AJIE (Asian Journal of Innovation and Entrepreneurship), 2017)
This research is an empirical spatial analysis of economic and social variables in the counties and cities in Java. The main variables used in this study is the economic growth, the average length of school and life expectancy. The analysis tool for estimating by using Geographic Information System (GIS) and Explatory Spatial Data Analysis (ESDA). Analysis with GIS is to map the distribution of socio-economic indicators with distribution quantile, while ESDA analyzing the condition of social and economic indicators with the Global Moran’s I Statistic Indicator and Local Spatial Association (LISA). The results of the analysis of the spatial distribution of economic and human capital development with Geographical Information System (GIS) showing the form of inequality between economic development and human capital. The results of the analysis of the spatial pattern of economic development and global human capital by moran’s i statistic shows the pattern shape clustered in urban and peri-urban areas. The results of the analysis of the spatial pattern of economic development and human capital with a local indicator of spatial association (LISA) shows the shape of the pattern of hot spots in urban areas especially in Jakarta, Yogyakarta and Surabaya and patterns of cold spots in areas that have the characteristics of rural districts.